2023
DOI: 10.1186/s13018-023-03499-w
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric measurement of lumbar pedicle in different regions: a systematic review

Abstract: Objective To collect the data of pedicle width and height in different areas, and to investigate the difference and variation rule of pedicle width and height. Methods Comprehensive search of PubMed, Ovid Medline, and Web of science databases was performed. Collected data were imported into SPSS, and one-way ANOVA test and post hoc test were used to determine whether there were statistical differences in pedicle width and height between the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…UBE-EFLIF technique comprises three portals, two of which are roughly 1.5 cm long and act as the endoscopic or working portal, positioned 2 cm outside the upper and lower pedicle. A supplementary portal, referred to as the “quarterback portal,” is created to facilitate the rotation of the cage to a horizontal orientation by making a 1 cm incision where the intervertebral space intersects the tangent line at the inner edge of the vertebral pedicle, 23 as seen in Figure 11.
Figure 11.The mainstream portal positions of the UBE-EFLIF approach 23 . (The dot size only provides a general indication and does not represent a specific proportion).
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…UBE-EFLIF technique comprises three portals, two of which are roughly 1.5 cm long and act as the endoscopic or working portal, positioned 2 cm outside the upper and lower pedicle. A supplementary portal, referred to as the “quarterback portal,” is created to facilitate the rotation of the cage to a horizontal orientation by making a 1 cm incision where the intervertebral space intersects the tangent line at the inner edge of the vertebral pedicle, 23 as seen in Figure 11.
Figure 11.The mainstream portal positions of the UBE-EFLIF approach 23 . (The dot size only provides a general indication and does not represent a specific proportion).
…”
Section: Resultsmentioning
confidence: 99%
“…
Figure 11. The mainstream portal positions of the UBE-EFLIF approach 23 . (The dot size only provides a general indication and does not represent a specific proportion).
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PS screws engage both cortical and trabecular bone, providing comprehensive fixation and enhancing stability, which may reduce the likelihood of screw failure. While studies evaluating CBT have been promising, justifying the increasing use of the technique, long-term studies of this approach have shown a relatively high failure rate [16][17][18][19]. Akpolat et al conducted a cadaveric study in 12 vertebrae from six cadaveric spines and found that CBT screws had a significantly decreased fatigue performance when compared to the PS screw control [12].…”
Section: Discussionmentioning
confidence: 99%